READMISSIONS TO ADOLESCENT PSYCHIATRIC INPATIENT CARE: A REGISTER STUDY - VISA VADÉN, RIITTAKERTTU KALTIALA, TIMO HOLTTINEN (Psychiatria Fennica)
ABSTRACT Objectives: Readmissions to inpatient care shortly after discharge are considered a problem. In psychiatry, repeated readmissions are referred to as a “revolving door” phenomenon and are assumed to illustrate failure of care. We set out to study readmissions in adolescent psychiatry. The aim of our study was to determine the proportion of patients who are readmitted to the hospital in general during adolescent years, and those who are readmitted within 30 days of discharge. We investigated the association of various sociodemographic, psychosocial, and symptom- and disorder-related factors with readmission. Materials and methods: We conducted a retrospective chart review of all patients admitted to the adolescent psychiatric ward at Tampere University Hospital from 2016 to 2020. We collected data on patient age, gender, family risk factors, diagnoses, symptoms and any new treatment episodes. We cross-tabulated gender, child protection involvement, diagnoses, symptoms and family risk factors with overall readmission, readmission within 30 days of discharge and the number of readmissions. To explore independent associations of the partially overlapping explaining variables, we used multivariable analyses. Results: Nearly half of the patients (48.4%) experienced a readmission during adolescent years. Thirteen per cent of patients were readmitted within 30 days of discharge. In bivariate associations female gender, diagnosis from schizophrenia group, diagnosis from somatoform disorder group and a child welfare contact predicted readmission in general. The only factor increasing readmission within 30 days of discharge was female gender. In the multivariable analyses, female gender, a diagnosis from the schizophrenia disorder group, mood disorder group, anxiety disorder group and somatoform disorder group predicted readmission. Additionally, symptoms of psychosis, self-harm and eating disorders increased the risk of readmission. Conversely, depressive symptoms and concerning alcohol and substance use were found to be protective against readmissions. Conclusions: In our study, the overall readmission rates were significantly higher than in many other studies. However, the 30-day readmission rates were closer to those found in other research. These differences are likely due to variations in patient populations, healthcare systems and treatment practices as well as a longer follow-up time used in the present study. Readmissions were predicted by severe disorders such as schizophrenia group and somatoform group disorders and self-harm. This suggests that illness-related factors play a major role. However, female gender predicted readmissions in general and within 30 days when disorder-related factors were accounted for. Such gender difference may warrant societal attention to gender inequalities.